Granulocyte Colony‐stimulating Factor‐dependent Growth of an Acute Myeloblastic Leukemia Cell Line - Nara, Nobuo (Jpn J Cancer Res, 1990)
We report herein the establishment and characterization of a granulocyte colony‐stimulating factor (G‐CSF)‐dependent acute myeloblastic leukemia (AML) cell line. The cell line, designated as OCI/AML 1a, has been cultured in the presence of G‐CSF and has shown exponential growth for over two years. The cells growing in suspension culture resembled myeloblasts on the basis of morphologic, cytochemical and surface phenotypic analyses. Other CSFs, interleukin‐3 and granulocyte‐macrophage colony‐stimulating factor did not support the growth of OCI/AML 1a cells so well as G‐CSF. The effect on the growth of OCI/AML 1a cells of G‐CSF was almost completely abolished by neutralizing monoclonal anti‐G‐CSF antibody. These findings showed that OCI/AML 1a cells required G‐CSF for growth. OCI/AML 1a cell line will be valuable for studies of the biological nature, proliferation and differentiation of leukemic cells. Furthermore, OCI/AML 1a cells should be useful for determining the mechanism by which G‐CSF induces the growth of hemopoietic cells.